Experimental and theoretical studies of unimolecular reactions of gas phase cluster ions. - Ochran, Richard Acquaah. (University of Ottawa (Canada), 2002)
The work presented in the following pages is the culmination of four years of research in the area of gas phase ion chemistry. During this period mass spectrometry and ab initio molecular orbital calculations were employed to investigate the unimolecular decomposition of proton-bound complexes between acetonitrile and methanol, ethanol, n-propanol, i-propanol, n-butanol, s-butanol, i-butanol, and t-butanol. Common to these systems, is a competition between dissociation of the hydrogen bond in the proton-bound dieter and isomerization to (CH3CNR)(H2O)+ (R=CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, butyl). The minimum energy reaction pathways for the isomerization in these systems are presented and compared. The dominant isomerization pathway for these ions is an internal SN2 reaction that proceeds via an intermediate CH3CN &cdots; ROH2+ ion (R=CH3, CH2CH 3, CH2CH2CH3, CH(CH3) 2). The mass spectra for the four butanol containing dimers (n-, s-, i-, and t-butanol) show similar behaviour. The effect of chlorine substitution on the acetonitrile on the four systems methanol, ethanol, n- and i-propanol were also investigated. The theoretical and experimental studies reveal a potential energy surface which is very similar to that obtained for the CH 3CN containing analogues (CH3CN)(CH3OH)H +, (CH3CN)(CH3CH2OH)H+, (CH3CN)(CH3CH2CH2OH)H+ and (CH3CN)((CH3)2CHOH)H +. The effect of chloro-substitution of the acetonitrile does not significantly affect the height of the rate limiting isomerization barrier which governs the water loss channel. The chloro-substitution however, lowers the proton affinity of the chloroacetonitrile and hence where there is competition between simple cleavage and isomerization, the protonated alcohol outcompetes the protonated chloroacetonitrile in the MI mass spectra. The dimer ion of acetonitrile and oxygen exhibit three peaks at m/z 32 (O 2), m/z 41, (CH3CN and ·CH2CNH +) and m/z 56 (-OH) in its MI mass spectrum. When O2 (triplet ground state) encounters a CH3CN+· or ·CH2CNH+ ion, the resulting complex (C2H3N)(O2)+· can take on either a doublet or quartet character. RRKM calculations predict a fast forward isomerization of CH3CN+· to ·CH2CNH+. The fact the dissociation and isomerization compete on the microsecond timescale is an indication that the reactions do not occur statistically and that RRKM theory does not apply.
Keywords: Chemistry, Physical.